2013
DOI: 10.1186/gb-2013-14-2-202
|View full text |Cite
|
Sign up to set email alerts
|

Studying the microbiology of the indoor environment

Abstract: The majority of people in the developed world spend more than 90% of their lives indoors. Here, we examine our understanding of the bacteria that co-inhabit our artificial world and how they might influence human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
151
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(162 citation statements)
references
References 74 publications
2
151
1
1
Order By: Relevance
“…It is estimated that humans in industrialized countries spend as much as 90% of their lives indoors (1,2). Indeed, for billions of humans, the "great indoors" comprises the new human ecosystem.…”
mentioning
confidence: 99%
“…It is estimated that humans in industrialized countries spend as much as 90% of their lives indoors (1,2). Indeed, for billions of humans, the "great indoors" comprises the new human ecosystem.…”
mentioning
confidence: 99%
“…The increasing ease and decreasing costs of high-throughput short-amplicon-sequencing technologies are propelling efforts to describe the microbial communities of surfaces on a massive scale (7). By parallel sequencing of short amplicons, typically 16S rRNA genes in bacteria and internal transcribed spacer (ITS) domains in fungi (8), it is possible to comprehensively profile the microbial composition of diverse environments.…”
mentioning
confidence: 99%
“…Culture media is defined as "a solid or liquid preparation used to grow, transport and store microorganisms" (Willey et al 2008, p. 110). Culture-based techniques are considered the standard for determining cell viability (Kelley and Gilbert 2013).…”
Section: Culture-based Methods Of Recoverymentioning
confidence: 99%
“…rDNA), for examining diversity can capture more organisms that culture-based studies miss, several orders of magnitude more diversity are found from these types of studies (Woese et al 1990;Kelley and Gilbert 2013). However, there are also limitations to culture-independent studies.…”
Section: Culture-based Methods Of Recoverymentioning
confidence: 99%
See 1 more Smart Citation